Ferroptosis determinants - potential therapeutic targets glioblastoma stem cells - V. E. Shevchenko; Z. N. Nikiforova; T. I. Kushnir; I. A. Kudryavtsev; A. A. Mitrofanov; A. Kh. Bekyashev; N. E. Arnotskaya (Успехи молекулярной онкологии)
Introduction. Treatment of glioblastoma multiforme remains little effective due to the rapidly developing recurrence of the tumor, due to its high tumorigenic potential, resistance to chemoradiation therapy and increased dissemination of glioma stem cells. The identification of potential therapeutic targets, which make it possible to more effectively destroy glioma stem cells, becomes topical. In this regard, the study of ferroptosis (FP), which can cause the death of tumor cells with a highly malignant phenotype, is of great importance. However, FP and its regulatory pathways in the GSC are not fully understood. At present, it is also not clear how FP differs for glioma stem cells and glioblastoma differentiated cells.Aim. To study the expression of ferroptosis signaling cascade determinants in CD133+ glioma stem cells and CD133- glioblastoma differentiated cells using high resolution proteomic mass spectrometry.Materials and methods. High-resolution proteomic mass spectrometry, cell technologies.Results. In total, 1970 proteins were identified, 15 of which are associated with ferroptosis and are present in both cell populations. Upregulation of 12 FP determinants (ACSL1, ACSL3, COPZ1, FTH1, FTL, GPX1, GPX4, PCBP1, SLC3A2, TFRC, VDAC1, VDAC2) was found in CD133+ glioblastoma stem cells compared to CD133- differential glioblastoma cells, 10 of which were more than 2-fold overexpressed.Conclusion. Important regularities have been established in the expression of ferroptosis determinants and proteins controlling this process in glioma stem cells, which can be used in the development of new approaches to the detection of potential targets for the therapy of glioblastoma multiforme.